Gnostic notes on temporal validity - Austin Jang; Molly Offer-Westort; Serena Wang; P. M. Aronow (Research & Politics)
Kevin Munger argues that, when an agnostic approach is applied to social scientific inquiry, the goal of prediction to new settings is generically impossible. We aim to situate Munger’s critique in a broader scientific and philosophical literature and to point to ways in which gnosis can and, in some circumstances, must be used to facilitate the accumulation of knowledge. We question some of the premises of Munger’s arguments, such as the definition of statistical agnosticism and the characterization of knowledge. We further emphasize the important role of microfoundations and particularism in the social sciences. We assert that Munger’s conclusions may be overly pessimistic as they relate to practice in the field.